1994
DOI: 10.1007/bf00335172
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arteriovenous malformations in children: report on 62 cases

Abstract: A series of 62 children with cerebral arteriovenous malformations admitted to our department in the course of 17 years (1975-1992) was reviewed in a retrospective study. In 54 cases hemorrhagic stroke was the first presenting symptom, followed by epilepsy in five cases. On admission 26 children presented with a neurological deficit, and 21 were admitted with a grade 3 status according to Botterell. Fifty-one malformations were supratentorial (41 hemispheric, 10 deep-seated) while 11 were infratentorial. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 36 publications
3
50
1
2
Order By: Relevance
“…7,19,22,25,30,34 According to reports, 0.1% of the population harbors an AVM, 3,8 and both sexes are equally affected. AVMs are the leading cause of nontraumatic intracerebral hemorrhage in people less than 35 years old.…”
mentioning
confidence: 99%
“…7,19,22,25,30,34 According to reports, 0.1% of the population harbors an AVM, 3,8 and both sexes are equally affected. AVMs are the leading cause of nontraumatic intracerebral hemorrhage in people less than 35 years old.…”
mentioning
confidence: 99%
“…The average age of onset of hemorrhagic stroke was 9.85 years with extremes of 2 months and 18 years [5][6][7][8][9]. The onset of symptoms was sudden or rapidly progressive in a few hours in all patients.…”
Section: Resultsmentioning
confidence: 99%
“…Hladky et al 9) documented two cases of recurrence, one located in the corpus callosum and the other located in the parietal lobe, among the 62 pediatric cases in which AVM surgery had been performed. They suggested that recurrence caused by microshunts might remain invisible on early postoperative angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Arteriovenous malformation (AVM) is the most frequent cause of hemorrhage in children 9) . Complete excision or obliteration of the lesion usually eliminates the risks of hemorrhage, and a negative cerebral angiogram is generally considered indicative of a cure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation